Providing a Model of Good Corporate Governance Maturity in the Iranian Insurance Industry (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The subject of this article is corporate governance maturity and its purpose is to provide a model of good corporate governance maturity in the insurance industry in Iran. The research is qualitative-exploratory and the method used in the present study is grounded theory or data foundation based on the approach of Strauss-Corbin. The research paradigm model based on Strauss and Corbin's approach included causal conditions, intervening factors, contextual conditions, strategies and actions of realization and consequences of realizing the maturity of corporate governance. Participants in this study were managers of Alborz, Asia, Pasargad, Parsian, Mellat insurance companies in Tehran. Using purposive sampling method, 12 interviewees were selected, which was obtained after 12 interviews with data saturation. The data collection tool in the qualitative section was a semi-structured interview. The interview was prepared and conducted according to an interview protocol. Also, in the present study, in order to assess the validity, the interview guide was sent to 10 experts and their opinions were used. The results of calculating the maturity indicators of good corporate governance are extracting a total of 721 open codes, 240 pivot codes and 69 selected codes. These data showed that providing benefits and compliance with laws and regulations, risk control and management, accepting social and corporate responsibility, not deviating from the rules, holding training courses and the culture of corporate governance. In explaining the results, they were related to causal conditions. The underlying factors were; Consensus and participation, ethical culture building, control and management, implementation of rules and regulations, revenue generation and benefits, periodic reporting, monitoring and improvement of methods, interaction with other countries, corporate readiness. Strategies were: Effective monitoring and control, law enforcement, securing benefits and increasing profits, human capital, benefiting from applied sciences, regulatory and facilitating factors, creating interaction. Outcomes were: Providing benefits, enforcing justice-oriented laws, accountability, professional ethics, effective and centralized oversight, increasing trust, growth of wealth and portfolio, use of technology, cooperation and participation, improving penetration and enforcement.